2016
DOI: 10.1162/jocn_a_00981
|View full text |Cite
|
Sign up to set email alerts
|

Coding of Visual, Auditory, Rule, and Response Information in the Brain: 10 Years of Multivoxel Pattern Analysis

Abstract: Abstract■ How is the processing of task information organized in the brain? Many views of brain function emphasize modularity, with different regions specialized for processing different types of information. However, recent accounts also highlight flexibility, pointing especially to the highly consistent pattern of frontoparietal activation across many tasks. Although early insights from functional imaging were based on overall activation levels during different cognitive operations, in the last decade many r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 122 publications
(139 reference statements)
7
69
1
1
Order By: Relevance
“…Importantly, if any of these scenarios could be confirmed empirically, this provided first-time evidence for human PFC representing entirely novel task rules in the initial phase of task practice. This contrasts with existing MVPA studies, which have shown that prefrontal cortex regions flexibly code currently task-relevant information, but this was confined to already well-familiarized task features 4,30,31 . A few pioneering studies have shown that such prefrontal representations are retrieved and re-cycled in the service of newly instructed tasks that rely on, or are recomposed of familiar task elements [32][33][34] .…”
Section: Introductioncontrasting
confidence: 86%
“…Importantly, if any of these scenarios could be confirmed empirically, this provided first-time evidence for human PFC representing entirely novel task rules in the initial phase of task practice. This contrasts with existing MVPA studies, which have shown that prefrontal cortex regions flexibly code currently task-relevant information, but this was confined to already well-familiarized task features 4,30,31 . A few pioneering studies have shown that such prefrontal representations are retrieved and re-cycled in the service of newly instructed tasks that rely on, or are recomposed of familiar task elements [32][33][34] .…”
Section: Introductioncontrasting
confidence: 86%
“…( 38 ) for a recent review]. To examine whether the voxels within these ROIs responded more strongly to words than false fonts, we performed a univariate analysis on (Chinese real words + English real words) versus (Chinese false fonts + English false fonts).…”
Section: Resultsmentioning
confidence: 99%
“…One study observed broad activations of lateral prefrontal and parietal cortices among highly suggestible individuals during response to a colour hallucination suggestion (McGeown et al, 2012). These regions comprise the frontal-parietal, executive attention, or multiple-demand network, a set of regions reliably activated across a range of operations (Woolgar, Jackson, & Duncan, 2016) and thereby imply that the suggestion was implemented through normal cognitive control mechanisms.…”
Section: Neurocognitive Bases Of Hypnosis and Hypnotic Suggestibilitymentioning
confidence: 99%